Carrageenan-Silica Hybrid Nanoparticles Prepared by a Non-Emulsion Method - Soares, Sofia F.
Spherical and monodispersed sub-micrometer sized particles of organic-inorganic hybrids were prepared by means of a sol-gel non-emulsion method using the biopolymer kappa-carrageenan and the alkoxysilane 3-isocyanatopropyltriethoxysilane (ICPTES). The structural characterization of the carrageenan-silica hybrid particles was performed by using FTIR spectroscopy and solid-state Si-29 and C-13 NMR spectroscopy and confirmed that.-carrageenan was covalently linked to the siliceous network via urethane bonds. Zeta-potential measurements indicate the hybrids were functionalized on the surface with sulfonate groups from the polysaccharide. These hybrids display thermal sensitivity, which is of great relevance for biomedical applications such as drug encapsulation and thermally controlled drug-delivery systems.